2021
DOI: 10.1021/acscatal.0c04279
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Water on Ru-Catalyzed Olefin Metathesis: Potent Deactivating Effects Even at Low Water Concentrations

Abstract: Ruthenium catalysts for olefin metathesis are widely viewed as water-tolerant. Evidence is presented, however, that even low concentrations of water cause catalyst decomposition, severely degrading yields. Of 11 catalysts studied, fast-initiating examples (e.g., the Grela catalyst RuCl 2 (H 2 IMes)(=CHC 6 H 4 -2-O i Pr-5-NO 2 ) were most affected. Maximum water tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 92 publications
(75 reference statements)
0
34
0
Order By: Relevance
“…have investigated a series of Ru catalysts and reported that the presence of water triggers the catalyst decomposition; therefore, the yield of product is affected (Scheme 6). They found that the bulkier iodine and cAAC catalyst is the best choice [67] . In continuation of their previous studies on iodine‐based Ru catalysts, Fogg et al.…”
Section: Areas Of Caac Chemistrymentioning
confidence: 76%
See 1 more Smart Citation
“…have investigated a series of Ru catalysts and reported that the presence of water triggers the catalyst decomposition; therefore, the yield of product is affected (Scheme 6). They found that the bulkier iodine and cAAC catalyst is the best choice [67] . In continuation of their previous studies on iodine‐based Ru catalysts, Fogg et al.…”
Section: Areas Of Caac Chemistrymentioning
confidence: 76%
“…They found that the bulkier iodine and cAAC catalyst is the best choice. [67] In continuation of their previous studies on iodine-based Ru catalysts, Fogg et al have synthesized second-generation ruthenium-diiodide catalysts (17) with cAAC and NHC ligands for the olefin metathesis in excellent yields. [68] Hong et al applied Grubbs-type and Hoveyda-type, cAAC stabilized ruthenium catalysts for olefin metathesis of 2,7divinyl-9,9-di-noctylfluorene (18) and 2,2',7,7'-tetravinyl-9,9'-spirobifluorene (19) in different ratios to synthesize seven copolymerization products in good to excellent yields (Scheme 7).…”
Section: Caac-stabilized Metal Complexes In Organic Catalysismentioning
confidence: 98%
“… 6 , 12 Indeed, their ethylene-tolerance is second only to that of cyclic (alkyl)(amino) carbene (CAAC) derivatives, examples of which appear in Chart 1 . 13 , 14 Heightened stability toward water 6 adds further potential, most prominently for opportunities in chemical biology.…”
mentioning
confidence: 99%
“…It is now seeing attention in challenging contexts ranging from pharmaceutical manufacturing to chemical biology and materials science . While chlororuthenium catalysts (Chart ) dominate these applications, iodide analogues offer important advantages. Long-overlooked because of their slower metathesis reactions, iodide catalysts such as nG-I 2 have recently been shown to offer improved productivities in the synthesis of macrocycles via ring-closing metathesis (mRCM, , a metathesis manifold of keen interest for the production of antiviral therapeutics), and increased selectivity for metathesis of terminal versus internal olefins . Their tolerance for ethylene , (the coproduct in metathesis of terminal olefins) is also striking: it is due in part to relatively slow bimolecular decomposition. , Indeed, their ethylene-tolerance is second only to that of cyclic (alkyl)­(amino) carbene (CAAC) derivatives, examples of which appear in Chart . , Heightened stability toward water adds further potential, most prominently for opportunities in chemical biology.…”
mentioning
confidence: 99%
See 1 more Smart Citation